MicroRNA-449a Overexpression, Reduced NOTCH1 Signals and Scarce Goblet Cells Characterize the Small Intestine of Celiac Patients - Capuano, Marina (Public Library of Science, 2011)
MiRNAs play a relevant role in regulating gene expression in a variety of physiological and pathological conditions including autoimmune disorders. MiRNAs are also important in the differentiation and function of the mouse intestinal epithelium. Our study was aimed to look for miRNA-based modulation of gene expression in celiac small intestine, and particularly for genes involved in cell intestinal differentiation/proliferation mechanisms. A cohort of 40 children (20 with active CD, 9 on a gluten-free diet (GFD), and 11 controls), were recruited at the Paediatrics Department (University of Naples Federico II). The expression of 365 human miRNAs was quantified by TaqMan low-density arrays. We used bioinformatics to predict putative target genes of miRNAs and to select biological pathways. The presence of NOTCH1, HES1, KLF4, MUC-2, Ki67 and beta-catenin proteins in the small intestine of CD and control children was tested by immunohistochemistry. The expression of about 20% of the miRNAs tested differed between CD and control children. We found that high miR-449a levels targeted and reduced both NOTCH1 and KLF4 in HEK-293 cells. NOTCH1, KLF4 signals and the number of goblet cells were lower in small intestine of children with active CD and in those on a GFD than in controls, whereas more nuclear beta-catenin staining, as a sign of the WNT pathway activation, and more Ki67 staining, as sign of proliferation, were present in crypts from CD patients than in controls. In conclusion we first demonstrate a miRNA mediated gene regulation in small intestine of CD patients. We also highlighted a reduced NOTCH1 pathway in our patients, irrespective of whether the disease was active or not. We suggest that NOTCH pathway could be constitutively altered in the celiac small intestine and could drive the increased proliferation and the decreased differentiation of intestinal cells towards the secretory goblet cell lineage.